Short-Chain Fatty Acids Differentially Affect Intracellular Lipolysis in a Human White Adipocyte Model - Jocken, Johan W. E.; González Hernández, Manuel A.; Hoebers, Nicole T. H.; van der Beek, Christina M.; Essers, Yvonne P. G.; Blaak, Ellen E.; Canfora, Emanuel E. (Frontiers in Endocrinology, 2018)
Background & Aims: Gut-derived short-chain fatty acids (SCFA), formed by microbial fermentation of dietary fibres, are believed to be involved in the aetiology of obesity and diabetes. Previous data from our group showed that colonic infusions of physiologically relevant SCFA mixtures attenuated whole-body lipolysis in overweight men. To further study potential mechanisms involved in the antilipolytic properties of SCFA, we aimed to investigate the in vitro effects of SCFA incubations on intracellular lipolysis and signalling using a human white adipocyte model, the hMADS cells. Methods: hMADS adipocytes were incubated with mixtures of acetate, propionate and butyrate or single SCFA (acetate, propionate and butyrate) in concentrations ranging between 1 μmol/L and 1 mmol/L. Glycerol release and lipase activation was investigated during basal conditions and following β-adrenergic stimulation. Results: SCFA mixtures high in acetate and propionate decreased basal glycerol release, when compared to control (P<0.05), whilst mixtures high in butyrate had no effect. Also, β-adrenergic receptor mediated glycerol release was not significantly altered following incubation with SCFA mixtures. Incubation with only acetate decreased basal (1 μmol/L) and β-adrenergically (1 μmol/L and 1 mmol/L) mediated glycerol release as compared to control (P<0.05). In contrast, butyrate (1 μmol/L) slightly increased basal and β-adrenergically mediated glycerol release compared with control (P<0.05), whilst propionate had no effect on lipolysis. The antilipolytic effect of acetate was accompanied by a reduced phosphorylation of hormone sensitive lipase (HSL) at serine residue 650. In addition, inhibition of Gi G proteins following pertussis toxin treatment prevented the antilipolytic effect of acetate. Conclusion: The present data demonstrated that acetate was mainly responsible for the antilipolytic effects of SCFA and acts via attenuation of HSL phosphorylation in a Gi coupled manner in hMADS adipocytes. Therefore, the modulation of colonic and circulating acetate may be an important target to modulate human adipose tissue lipid metabolism.